2015
DOI: 10.1111/acer.12673
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Moderates Genetic and Environmental Effects on the Amount of Alcohol Use

Abstract: Background Much is unknown about the relationship between socioeconomic status (SES) and alcohol use, including the means by which SES may influence risk for alcohol use. Methods Using a sample of 672 twin pairs (aged 25–74) derived from the MacArthur Foundation Survey of Midlife Development in the United States (MIDUS), the present study examined whether SES, measured by household income and educational attainment, moderates genetic and environmental influences on three indices of alcohol use: amount used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
5
18
0
Order By: Relevance
“…A familial predisposition of problematic alcohol use or parental psychiatric disorders may be underlying factors that influence both AUD and low SES [8]. Probably, some individuals have a greater genetic vulnerability, which can be triggered by environmental stressors [29]. However, in the present study the potential effect of SES on AUD still remained after taking familial factors into account, and after controlling for previous AUD, suggesting that adulthood SES is likely to have an independent effect on risk for AUD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A familial predisposition of problematic alcohol use or parental psychiatric disorders may be underlying factors that influence both AUD and low SES [8]. Probably, some individuals have a greater genetic vulnerability, which can be triggered by environmental stressors [29]. However, in the present study the potential effect of SES on AUD still remained after taking familial factors into account, and after controlling for previous AUD, suggesting that adulthood SES is likely to have an independent effect on risk for AUD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from England concluded that educational attainment was the strongest predictor of consumed volume of alcohol and binge drinking frequency [30]. General intelligence and cognitive abilities may act as mediating factors, as well as individual non-shared environmental factors, such as social contacts and hobbies [22, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Education has been shown to moderate genetic variance in drinks per week (Johnson et al, 2010a), drinking amount (Hamdi et al, 2015), smoking initiation (McCaffery et al, 2008), and smoking quantity (Johnson et al, 2010a) such that genetic influences were greater under conditions of low education, providing support for the diathesis-stress model. In a young adult sample, education moderated environmental, but not genetic, variance in both alcohol-related problems and the maximum number of drinks consumed in 24 hours such that environmental factors were stronger at lower levels of educational attainment (Latvala et al, 2011).…”
Section: Education and Healthmentioning
confidence: 99%
“…The interactions between genes and environment have a particularly influential role on mean levels of IE because environmental stressors can activate genetic vulnerabilities. For example, high-risk environments (e.g., low socioeconomic status or urban environments) have been found to amplify genetic predispositions to externalizing behaviors (Hamdi, Krueger, & South, 2015; Legrand, Keyes, McGue, Iacono, & Krueger, 2008), whereas environments that limit choice (e.g., rural environments or high parental monitoring) attenuate genetic influences on externalizing (Dick et al, 2007; Rose, Dick, Viken, & Kaprio, 2001). Beyond these diathesis–stress mechanisms, there are also some preliminary findings that suggest specific genes and biological mechanisms may increase individuals’ sensitivity to the influence of positive or negative environments (e.g., Caspi et al, 2002; Keiley, Howe, Dodge, Bates, & Petti, 2001; Obradovic et al, 2011).…”
Section: A Developmentally Informed Approach Based On the Empiricallymentioning
confidence: 99%